Micronutrient Density of the Global Food Supply - Nick W. Smith; Ty Beal (Food Frontiers)
ABSTRACT Global diets are inadequate in micronutrients, leading to deficiencies and related diseases. Addressing these micronutrient shortfalls requires increasing the nutrient density of the global food supply. Inferring micronutrient supply based on food balance sheet data is widespread practice in nutrition modelling, whereas designing food‐based interventions is usually done using dietary data. Here, we provide an online interactive tool for investigating the micronutrient density of food balance sheet items, to help identify appropriate food supply interventions to increase the availability of micronutrient‐dense foods globally. While the tool can be used for up to 28 food components (including macronutrients), we demonstrate its use by ranking food balance sheet items based on their combined content of 17 micronutrients per 100 g or per 100 kcal. High ranking foods varied between the mass and energy lists, but included offals, seeds, nuts, seafood, and non‐starchy vegetables. The tool can be used by nutrition researchers to identify foods with the potential for supplying the specific combinations of micronutrients needed by at‐risk populations.